Contraception need and available services among incarcerated women in the United States: a systematic review - Mishka S. Peart; Andrea K. Knittel (BMC, 2020)
Abstract Context Seventy-five percent of incarcerated women are of reproductive age, most of whom are at-risk for unintended pregnancy. Women who are incarcerated come disproportionately from socioeconomically disadvantaged backgrounds and often lack access to desired reproductive health care. While the carceral system provides a unique opportunity to fill this gap, a better understanding of the contraceptive needs, desires, and plans of incarcerated women is needed to optimize health care provision within the carceral system. A review of current contraceptive services available to women inmates may both identify model care programs and shed light on areas for improvement. Evidence acquisition PubMed electronic database used to identify relevant articles published between January 1975 and September 2019 using a systematic review method. Results Twenty-five articles met the inclusion criteria and answered four key questions surrounding contraception in the carceral system. Most articles (48%) represented scientific research. Other publications identified by this review were expert commentaries, policy briefings, guidance and recommendations reports, and law and bioethics reviews. Conclusions Incarcerated women desire access to standard and emergency contraception from carceral health care systems. Knowledgeable family planning practitioners providing patient-centered and trauma-informed care and public health interventions linking newly released inmates to community clinics can help alleviate inmates' concerns regarding initiating desired contraception while incarcerated.